An Evaluation of A Government Performance Accountability System Indonesian District Governments 2010 - Toni Triyulianto (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The goal of this paper is to provide better information of Government Performance Accountability System (SAKIP) implementation in Indonesian District Governments to policy makers. This study utilizes the evaluation result of Government Performance Accountability System (SAKIP) 2010 to analyze the effort of 273 District governments in Indonesia in implementing the SAKIP.The research question of this paper is: do auditor’s opinion and number of population have significant different to the SAKIP score? To investigate what factors that determine the score of Government Performance Accountability System (SAKIP), several theories as well as a logical thinking were taken to figure out the research question. Those theories as well as logical thinking reveal that revenue and spending, seize of population, area, poverty level, human development index, auditor’s opinion, number of government employee and education level government employee tend to correlate the SAKIP score.Two hypotheses have been chosen in this paper: 1) higher level in Auditor’s Opinion more likely will increase the SAKIP score evaluation, and 2) size of Population has significant different to the SAKIP score. Result shows we have to reject all the null hypotheses.